Pengaruh Nilai Tukar Terhadap Kinerja Keuangan Pt Darma Henwa Tbk - Istiono; Dava Rizqi Al Fajri; Azarya Bartholomeus Djonien (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
This study aims to analyze the impact of the exchange rate (IDR/USD), interest rates (BI Rate), coal prices, global inflation, and liquidity (Current Ratio) on the financial performance of PT Darma Henwa Tbk, proxied by Return on Assets (ROA). The study employs multiple linear regression analysis using quarterly data from 2018 to 2025, sourced from financial reports from the Indonesia Stock Exchange (IDX), Bank Indonesia, and Bloomberg. The results indicate that coal prices and liquidity have a significant positive effect on ROA, whereas the exchange rate, interest rates, and global inflation have a significant negative effect. The model yields a coefficient of determination (R²) of 0.782, indicating that 78.2% of the variation in ROA can be explained by these five variables. These findings support the relevance of Signaling Theory and Arbitrage Pricing Theory within the Indonesian mining services sector and offer strategic implications for management regarding exchange rate risk mitigation and liquidity management.